Role of nucleus accumbens core but not shell in incubation of methamphetamine craving after voluntary abstinence - Rossi, Ludovica Maddalena (Neuropsychopharmacology, 2019)
We recently introduced an animal model to study incubation of drug craving after prolonged voluntary abstinence, mimicking the human condition of relapse after successful contingency management treatment. Here we studied the role of the nucleus accumbens (NAc) in this model. We trained rats to self-administer a palatable solution (sucrose 1% + maltodextrin 1%, 6 h/day, 6 days) and methamphetamine (6 h/day, 12 days). We then evaluated relapse to methamphetamine seeking after 1 and 15 days of voluntary abstinence, achieved via a discrete choice procedure between the palatable solution and methamphetamine (14 days). We used RNAscope in-situ hybridization to quantify the colabeling of the neuronal activity marker Fos, and dopamine Drd1- and Drd2-expressing medium spiny neurons (MSNs) in NAc core and shell during the incubation tests. Next, we determined the effect of pharmacological inactivation of NAc core and shell by either GABA(A) and GABA(B) agonists (muscimol + baclofen, 50 + 50 ng/side), Drd1–Drd2 antagonist (flupenthixol, 10 µg/side), or the selective Drd1 or Drd2 antagonists (SCH39166, 1.0 µg/side or raclopride, 1.0 µg/side) during the relapse tests. Incubated methamphetamine seeking after voluntary abstinence was associated with a selective increase of Fos expression in the NAc core, but not shell, and Fos was colabeled with both Drd1- and Drd2-MSNs. NAc core, but not shell, injections of muscimol + baclofen, flupenthixol, SCH39166, and raclopride reduced methamphetamine seeking after 15 days of abstinence. Together, our results suggest that dopamine transmission through Drd1 and Drd2 in NAc core is critical to the incubation of methamphetamine craving after voluntary abstinence.